Chlopi - Reymont, Wladyslaw Stanislaw, 1867-1925.; Ziejka, Franciszek, 1940- (Wroclaw : Zaklad Narodowy im. Ossolinskich, 1991)
A classic novel by the Nobel Prize author, about the Polish peasants.
t. 1., cz. 1. Jesien -- cz. 2. Zima -- t. 2., cz. 3. Wiosna -- cz. 4. Lato.
Includes bibliographical references (v. 2, p. cxxvi-cxxvii).
Keywords: Historical fiction, Polish